The Effect of Mathematical Anxiety on the Understanding of Mathematical Concepts in Class XI Students of SMAN 5 Sinjai - Hariani Harjunar; Inayanti Fatwa (EduLine: Journal of Education and Learning Innovation, 2022)
This research aims to determine the influence of mathematical anxiety on the understanding of mathematical concepts. The method used an investigation and sampling method with a simple random sampling technique, the sample of which was 90 students. Analysis in the context of testing research hypotheses using linear regression analysis tests, with the results of hypothesis tests producing the influence of mathematical anxiety on the understanding of mathematical concepts.